Generation of human iPSCs from urine derived cells of a non-affected control subject - Afzal, Muhammad Zeeshan; Gartz, Melanie; Klyachko, Ekaterina A.; Khan, Sadiya Sana; Shah, Sanjiv J.; Gupta, Sweta; Shapiro, Amy D.; Vaughan, Douglas E.; Strande, Jennifer L. (Stem cell research, 2017)
We have generated a human induced pluripotent stem cell (iPSC) line under feeder-free culture conditions using the urine derived cells (UCs) collected from non-affected control subjects to use as a comparison group for the iPSC lines containing a Plasminogen Activator Inhibitor-1 (PAI-1 homozygous/heterozygous) mutation. The Sendai Virus (SeV) vector encoding pluripotent Yamanaka transcription factors was used at a low multiplicity of infection to reprogram the UCs.